(3cJGH GdHGg heG jMJGL Gdjg ef JOHjQ GdHQb aj GSJYeGdIs - (3bSWG Hf dhbG GdHYdHcj,J (B300 (3g` s ((3ejNGFjd Hf jhMfG GdeGdci GdeJWHH s)
(3ChdgG (B:s
(3bGd bSWG Hf dhbG(B: (3cd WGdH hHGMK aWdHg hjMKg efGSH dWHjYJg hfaSI aGdWHjYI GdaGVdI hGdfaS GdPcjI s
(3BNQgG (B:s
(3jOb hjYLf HYSd efRhY GdQZhI GdTQHI efg HbOQ MhRJjf s
(3cJHg deMeO Hf CMeOs
(3cGJH HWQjbg GdHWGQbIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B131s
Keywords: (3GdWHs